2004
DOI: 10.1210/en.2004-0900
|View full text |Cite
|
Sign up to set email alerts
|

Minireview: PRKAR1A: Normal and Abnormal Functions

Abstract: The type 1alpha regulatory subunit (RIalpha) of cAMP-dependent protein kinase (PKA) (coded by the PRKAR1A gene) is the main component of type I PKA, which regulates most of the serine-threonine kinase activity catalyzed by the PKA holoenzyme in response to cAMP. Carney complex (CNC), or the complex of spotty skin pigmentation, myxomas, and endocrine overactivity, is a multiple endocrine (and not only) neoplasia syndrome that is due to PRKAR1A-inactivating mutations. The R1alpha protein and PRKAR1A mRNA have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
170
0
6

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(178 citation statements)
references
References 77 publications
2
170
0
6
Order By: Relevance
“…Although PKARI␣ may act as a "tumor suppressor" in CNC, previous studies have also reported that PKARI␣ facilitates the cell proliferative signaling of hormones and growth factors in certain types of cancer cells (46) and depletion of PKARI␣ effectively inhibits transcription of certain genes and growth of tumor cells (47). Thus, PKARI␣ may augment or inhibit cellular proliferation in a cell type-specific manner.…”
Section: Pp2a Exists In a Complex With Rsk1⅐pka⅐d-akap1 And Ht31mentioning
confidence: 99%
“…Although PKARI␣ may act as a "tumor suppressor" in CNC, previous studies have also reported that PKARI␣ facilitates the cell proliferative signaling of hormones and growth factors in certain types of cancer cells (46) and depletion of PKARI␣ effectively inhibits transcription of certain genes and growth of tumor cells (47). Thus, PKARI␣ may augment or inhibit cellular proliferation in a cell type-specific manner.…”
Section: Pp2a Exists In a Complex With Rsk1⅐pka⅐d-akap1 And Ht31mentioning
confidence: 99%
“…It can occur in isolated form, or as the main component of Carney syndrome [4]. Carney syndrome is an autosomal dominant disease caused by inactivating mutations of the PRKAR1A gene (chromosome 17q22-24) [6]. The PRKAR1A gene encodes the regulatory subunit of kinase-A [7].…”
Section: Discussionmentioning
confidence: 99%
“…Em cerca de 60% dos pacientes com CC, uma mutação foi identi-ficada no gene da proteína kinase dependente de cAMP (PRKAR1A), principal mediador do sistema cAMP, diretamente envolvido na via de sinalização de ACTH. Mutações no gene PRKAR1A, localizado no 17q22-24, foram identificadas em adenomas adrenais, porém não em carcinomas adrenais; por outro lado, LOH dessa região foi encontrada em 23% dos adenomas e em 53% dos carcinomas adrenocorticais (37,38).…”
Section: Bases Moleculares Dos Tumores Adrenocorticaisunclassified